Prevalence of Hepatitis B and Hepatitis C Viruses in ?-thalassemia Major Patient in AD-Diwanya province, Iraq - Hassan Raji Jallab1 , Zahraa Muayad Eesa1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: transmition of infectious agent is still the most common cause of death and disability related to blood transfusion.Objective: to estimate the prevalence of HBV and HCV in beta thalassemic major patients in Ad-Diwayah governorate.Method: The current study is a retrospective cross sectional study involving sample of 80 thalassemic major patients who regularly visit thalassemia center in Ad-diwuryah for treatment, data that required in the study had been collected from patients, their guardians and from the records.Results: The prevalence rate of HBV was 2.5% (l male and 1 Female ) which was significantly associated with family history of hepatitis ; while the prevalence rate of HCV was 3.8% (1male and 2 female) which was significantly associated with age and family history of hepatitis.